The “Character Garden” program as an environmentally based character education innovation in elementary schools - Elan Elan; Riefki Fiestawa; Risbon Sianturi; Qonita Qonita; Pidi Mohamad Setiadi (Universitas Muhammadiyah Malang, 2025)
Character education in elementary schools still faces obstacles due to the dominance of lecture methods and a lack of contextual learning experiences. The Character Garden Program was developed as a community service innovation to strengthen teachers' capacity in integrating character values ​​through school garden-based learning in Indihiang District, Tasikmalaya City. The activity was implemented using a Participatory Action Research (PAR) approach involving lecturers, teachers, principals, and the education community. A total of 39 teachers from seven elementary schools participated in training, module development, and implementation of the character garden in their respective schools. The results showed a significant increase in teachers' understanding of character education integration, with an average pre-test score of 61.05 increasing to 77.24 (p < 0.001). Among students, responsible behavior increased from 2.61 to 3.40, and mutual cooperation from 2.63 to 3.36. Teachers also reported positive changes in the form of increased student discipline and environmental awareness. This program produced a Character Garden module that has been used in seven schools and registered as IPR. This activity has had an impact on improving teachers' pedagogical competence and the formation of a character-based school culture. The next program recommendation is to expand the implementation of the Character Garden by utilizing teacher working groups to implement learning activities that foster character education in a concrete way. Long-term mentoring is also needed to strengthen the program's sustainability and evaluate the impact of student character in real-life contexts.